Transport, electrochemical and thermophysical properties of two N-donor-functionalised ionic liquids - Rüther, T.; Harris, K.; Horne, M.; Kanakubo, M.; Rodopoulos, T.; Veder, Jean-pierre; Woolf, L. (Wiley - V C H Verlag GmbH & Co. KGaA, 2013)
Two N-donor-functionalised ionic liquids (ILs), 1-ethyl-1,4- dimethylpiperazinium bis(trifluoromethylsulfonyl)amide (1) and 1-(2-dimethylaminoethyl)-dimethylethylammonium bis(trifluoromethylsulfonyl)amide (2), were synthesised and their and transport properties measured. The data were compared with the benchmark system, N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide (3). Marked differences in thermal and electrochemical stability were observed between the two tertiary-amine- functionalised salts and the non-functionalised benchmark. The former are up to 170 K and 2 V less stable than the structural counterpart lacking a tertiary amine function. The ion self-diffusion coefficients (Di) and molar conductivities (?) are higher for the IL with an open-chain cation (2) than that with a cyclic cation (1), but less than that with a non-functionalised, heterocyclic cation (3). The viscosities (?) show the opposite behaviour. The Walden [??(1/?)t] and Stokes-Einstein [Di/T)?(1/?)t] exponents, t, are very similar for the three salts, 0.93-0.98 (±0.05); that is, the self-diffusion coefficients and conductivity are set by ?. The Di for 1 and 2 are the same, within experimental error, at the same viscosity, whereas ? for 1 is approximately 13 % higher than that of 2. The diffusion and molar conductivity data are consistent, with a slope of 0.98±0.05 for a plot of ln(?T) against ln(D++D -). The Nernst-Einstein deviation parameters (?) are such that the mean of the two like-ion VCCs is greater than that of the unlike ions. The values of ? are 0.31, 0.36 and 0.42 for 3, 1 and 2, respectively, as is typical for ILs, but there is some subtlety in the ion interactions given 2 has the largest value. The distinct diffusion coefficients (DDC) follow the order Dd- < Dd++ < D d+-, as is common for [Tf2N]- salts. The ion motions are not correlated as in an electrolyte solution: instead, there is greater anti-correlation between the velocities of a given anion and the overall ensemble of anions in comparison to those for the cationic analogue, the anti-correlation for the velocities of which is in turn greater than that for a given ion and the ensemble of oppositely charged ions, an observation that is due to the requirement for the conservation of momentum in the system. The DDC also show fractional SE behaviour with t~0.95. N-Donor-functionalised ionic liquids: The physicochemical properties of a cyclic and a noncyclic N-donor ionic liquid of similar molecular weight were examined and compared with the nonfunctionalised benchmark system, N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide. Marked differences in thermal and electrochemical stability were observed (see graphic). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.